THE EFFECT OF MANAGERIAL OVERCONFIDENCE ON CORPORATE INVESTMENT - Mochamad Ali Fudin Al Islami; Muhammad Madyan (Manajemen Bisnis, 2020)
The research aims to analyze the impact of managerial overconfidence on corporate investment (investment scale, overinvestment and underinvestment) using companies listed in Indonesia’s Stock Exchange in 2012-2018 as a sample. The analysis method used Ordinary Least Square and robustness test used Maximum Likelihood  Estimation. The result shows that managerial overconfidence has a significantly positive impact on the corporate investment scale. It means that managerial overconfidence makes overinvestment problem more severe (more inefficient) and underinvestment problem less severe (more efficient).